A sympatric species pair: Spogostylum ocyale (Wiedemann, 1828) and S. griseipenne Macquart, 1850 (Diptera: Bombyliidae) - Greathead, D. J. (Zootaxa, 2003)
Type specimens of Spogostylum ocyale (Wiedemann) and S. griseipenne (Macquart) were examined and found to be distinct species. Characters separating them are provided and they are shown to be largely sympatric. Spogostylum umbra (Walker) and S. arugotense Zaitzev are confirmed as synonyms of S. ocyale and some published misidentifications are corrected.